2023
DOI: 10.3390/ijms241310777
|View full text |Cite
|
Sign up to set email alerts
|

Effects of miR-33 Deficiency on Metabolic and Cardiovascular Diseases: Implications for Therapeutic Intervention

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that post-transcriptionally inhibit gene expression. These small molecules are involved in several biological conditions such as inflammation, cell growth and proliferation, and regulation of energy metabolism. In the context of metabolic and cardiovascular diseases, miR-33 is of particular interest as it has been implicated in the regulation of lipid and glucose metabolism. This miRNA is located in introns harboured in the genes encoding sterol regulatory element-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…Induction of miR-33 expression inhibits the expression of several target genes; some are involved in reverse cholesterol transport in macrophages (ATP-binding cassette transporter ABCA1 and ABCG1), while others are implicated in fatty acid metabolism such as carnitine palmitoyltransferase 1A (CPT1A), hydroxyacyl-CoA-dehydrogenase (HADHD), and carnitine O-octanoyltransferase (CROT). By inhibiting such targets, miR-33 is responsible for the increase in the size of atheroma plaques and hepatic lipid accumulation through impaired insulin response (it represses phosphorylation of IRS-2 and AKT) ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of miR-33 expression inhibits the expression of several target genes; some are involved in reverse cholesterol transport in macrophages (ATP-binding cassette transporter ABCA1 and ABCG1), while others are implicated in fatty acid metabolism such as carnitine palmitoyltransferase 1A (CPT1A), hydroxyacyl-CoA-dehydrogenase (HADHD), and carnitine O-octanoyltransferase (CROT). By inhibiting such targets, miR-33 is responsible for the increase in the size of atheroma plaques and hepatic lipid accumulation through impaired insulin response (it represses phosphorylation of IRS-2 and AKT) ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…For several decades, we based many of our clinical decisions on classical biomarkers of liver injury with low sensibility and specificity. Animal trials all showed important deregulation of specific miRNAs in rats fed with high-fat or high-fructose diets ( 15 , 16 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…miR-483-5p targets ERK1 and positively regulates PPARγ expression and promotes adipogenesis in mouse preadipocyte 3T3-L1 cells and human adipose-derived MSCs [56,70]. miR-33 may prevent the onset of obesity [71]. Compared to control mice, miR-33-deficient mice are more likely to become obese due to increased food intake caused by an increased secretion of orexigenic hormones, such as ghrelin, or leptin resistance [66].…”
Section: Mirnas and Obesitymentioning
confidence: 99%
“…ApoAI is known to exclusively act as a cholesterol acceptor for ABCA1 [ 14 ] and so strategies to increase ABCA1 expression within MLC may result in atheroprotection via removing intracellular cholesterol through enhanced apoAI-mediated cholesterol efflux. The microRNA miR-33a-5p is well-recognized to silence ABCA1 expression [ 15 ]. Interestingly, miR-33a-5p is capable of silencing ABCG1 expression in rodents, but not in humans, while extensive published literature implies SR-BI to not be a likely target gene for miR-33a-5p [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%